Impact of Wind Speed Measurement Resolution on Estimated Capacity Factor and Electricity Production Cost. Issue 6 (October 2013) - Akdağ, Seyit Ahmet; Güler, Önder
This paper presents the results of the estimated capacity factor differences of 55 wind turbines for nine resolutions of wind speed data. It is found that the utilization of low resolution mean wind speed data for energy output estimation may cause critical errors. Since wind speed is highly variable in time, utilization of low resolution mean wind speed data inevitably leads to a smoothing of the data, thus leading a loss of information and wind characteristics. The estimated capacity factor of wind turbines and the mean power density of a region can therefore change with data resolution. Noticeable capacity factor and wind power density differences were found among different resolution data sets. Therefore, high resolution mean wind speeds should be used when evaluating the economic and technical viability of wind energy project.